REKAYASA GENETIK PADA NYAMUK PENYEBAB MALARIA - Romadhona, Harisma Atiqur; Qushayyi, Muhammad Faiq; Sari, Rahmawati Yanita; rohmah, sayyidah auliyar (Poltekkes Kemenkes Malang, 2024)
Indonesian is a country with a heterogeneous tropical climate and is also vulnerable to the impacts of regional and global climate change. Malaria is transmitted by Anopheles sp. mosquitoes, with clinical and pathological symptoms of malaria almost exclusively caused by the asexual phase of plasmodium in erythrocytes. This research uses a qualitative descriptive approach. Because the data used comes from the description of words. Using the type of library research or library research. This type of research is used to collect data related to the object of research that has a library nature. Library research and literature searches are not only carried out for the initial steps of preparing a research framework, but at the same time become a library source used as a source of research data. Genetic engineering is a technology that involves the manipulation of DNA molecules, also known as recombinant DNA technology. Various terms are used to refer to this technique, including gene manipulation, DNA recombination, gene cloning and gene modification. . Genetic engineering uses basic methods, such as DNA isolation, PCR, RT-PCR, hybridisation techniques, and RFLP analysis. Genetic engineering in mosquitoes can be done in several ways, namely: sterile male technique, distribution of mosquitoes with dominant lethal genes, and gene drives.